Politics and education in Antonio Gramsci. Regarding Antonio Gramsci: A pedagogy to change the World - Gómez, Sebastián (International Gramsci Journal, 2023)
This article is a review of the book Antonio Gramsci: A Pedagogy to Change the World (2017) edited by Nicola Pizzolato and John Holst, which brings together contributions from specialists in Gramscian educational thought from different language-regions: English, Italian, French and Latin American. Seeking to contextualize the book, the articles reconstruct the main features of the reception of Gramscian thought in the Anglophone world. This shows the vast Anglophone tradition in employing Gramsci not only in the political or cultural field, but also in the educational one. It also suggests that this tradition has reached our days, the Anglophone world being one of the main spaces in the study and use of Gramsci. The article, furthermore, outlines Gramsci’s legacy as a truly international challenge. In this sense, the book suggests a Gramscian problem that has gained an important influence in Gramscian studies over the last few decades, particularly in Italy and the Anglophone world: that of translation. This translation among intellectuals from various countries is not, to paraphrase Gramsci, “perfect” but it is essential in order to understand and assume our contemporary political-pedagogical challenges.